Formation of the wheat productivity of an ear of winter wheat plants depending on the time of planting and seeding rate - Рожков, А. О.; Бобро, М. А.; Рижик, Т. В. (Scientific Progress & Innovations, 2016)
The article presents the results of studies conducted during 2007–2009, 2014 in the experimental field of HNAU named after V. V. Dokuchayev regarding the impact of the application of different sowing date and seeding rates on the variability of ear productivity indicators of different systems of soft winter wheat stalks of variety Astet. Formation of the highest levels of ear productivity of main and side stems of the average for the year of studies was provided on 15–17 September with the sowing seed rate 5,0 million grains/ha. The effectiveness of the seeding rate by years of research was more stable compared to the timing of sowing, the impact of which is significantly dependent on the weather conditions of the growing season of a particular year.